2016
DOI: 10.1007/978-3-319-39919-5_3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Integrated Communication on Entrepreneurial Companies’ Financial Performance: A Developing Economy

Abstract: This volume  Focuses on latest developments and challenges in global financial environment  Presents studies on latest topics such as contagion risk transmission, oil-price development, and entrepreneurial finance

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 11 publications
0
5
0
1
Order By: Relevance
“…According to Lwamba et al , both financial and non-financial performance will be enhanced with the continued adoption of market strategies that will take OE ahead to grow market share. Furthermore, the collective and integrated efforts associated with the proactivity of IFC will see to the identification of new opportunities to create sustainable competitive advantage (Migliori et al , 2019), and thus performance (Marjanova et al , 2015). The findings which differ from the literature could suggest that aspects of organisational culture, systems, processes, structure, management styles and decision-making approaches impact the degree of cooperation and seamless communication among employees, departments and functions in this context (Kanovska and Tomaskova, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Lwamba et al , both financial and non-financial performance will be enhanced with the continued adoption of market strategies that will take OE ahead to grow market share. Furthermore, the collective and integrated efforts associated with the proactivity of IFC will see to the identification of new opportunities to create sustainable competitive advantage (Migliori et al , 2019), and thus performance (Marjanova et al , 2015). The findings which differ from the literature could suggest that aspects of organisational culture, systems, processes, structure, management styles and decision-making approaches impact the degree of cooperation and seamless communication among employees, departments and functions in this context (Kanovska and Tomaskova, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Migliori et al (2019) iterate the criticality of IFC in integrating all the business functions and units to address market requirements, as informed by customer needs through capability, capacity, knowledge and resource sharing. Furthermore, Marjanova et al (2015) advocate that IFC is important for performance enhancement, profitability and competitiveness. Therefore, the following hypotheses are formulated:…”
Section: H3b Oe Positively Influences Bp (Non-financial)mentioning
confidence: 99%
“…Corporate culture memiliki makna berupa komitmen dan trust pada rekan kerja. Marjanova et al (2015) mengemukakan semakin tinggi IFC maka akan semakin tinggi performa perusahaan yang berhubungan dengan efektifitas dan efisiensi kerja. Hal ini menghasilkan beberapa keuntungan bagi perusahaan minyak dan gas bumi, yaitu meningkatkan kuantitas hasil produksi, analisis yang lebih detail terhadap permasalahan yang terjadi di perusahaan, persiapan yang lebih matang untuk melakukan strategi pengeboran, peningkatan pemrosesan, pemberian informasi internal perusahaan, peningkatan pengambilan keputusan, dan peningkatan terhadap orientasi strategi jangka panjang.…”
Section: Pendahuluanunclassified
“…, 2020) and that it is influenced by the information disclosure policy. The use of integrated reporting (IR) can lead to increased profitability of companies (Marjanova et al. , 2017), while the analysis of profitability indicators and other financial indicators in correlation with non-financial variables may facilitate the ranking of companies.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the disclosure degree of environmental, social, economic and governance (ESEG) information is a frequently investigated topic in correlation with performance indicators, as other studies revealed that financial performance (FP) is a significant indicator of the financial health of companies (S ¸tefan, 2016;Sab au-Popa et al, 2020) and that it is influenced by the information disclosure policy. The use of integrated reporting (IR) can lead to increased profitability of companies (Marjanova et al, 2017), while the analysis of profitability indicators and other financial indicators in correlation with nonfinancial variables may facilitate the ranking of companies.…”
Section: Introductionmentioning
confidence: 99%